PENGARUH MEKANISME INTERNAL TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR 2011-2013) - Wisnu Agung Indra Purbaya Atmaja Putra; Endang Kiswara (Diponegoro Journal of Accounting, 2015)
This study aims to obtain empirical evidence about the influence of internal mechanism of corporate governance  which consists of proportion of board of commissioner independent, board of commissioner, managerial ownership. This research is a replication with modification of the research Abed (2012) that examined the influence of good corporate governance to earnings management which is proxied by discretionary accrualsThe population of this research was all companies listed in Indonesia Stock Exchange (ISX) 2011-2013. Sample of this research was all of manufacturing company which listed at Indonesia Stock Exchange (ISX) 2011-2013. The total samples were 43 companies and 129 observations of financial statements. Data Analysis was performed with hypothesis testing used multiple regression analysis. Statistic program in this study used SPSS 21.The result of this research showed that proportion of board of commissioner independent and managerial ownership has negative impact and significant to earnings management. While board of commissioner, and also two variables control which are used in this research, firm size and leverage do not have significant effect to earnings management. This research showed that practice of corporate governance was still minimal to control the practice of earnings management.